PENGARUH PROMOSI JABATAN TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN KOMUNIKASI DAN INFORMATIKA REPUBLIK INDONESIA JAKARTA - Jumiyati Jumiyati; Yunidyawati Azlina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
The purpose of this study was to determine whether or not there was an influence between promotions on employee performance at the Ministry of Communication and Information of the Republic of Indonesia Jakarta. The research method used in the preparation of this Final Project is a quantitative method. The sampling technique uses simple random sampling. The distribution of quetionnnaires is limited to employess of the staffing bureau and organization amounting to 150 employees, samples were taken using the Slovin formula to be 60 employees. Data is processed with SPSS version 23. From the correlation test results of 0.755 the value is included in the strong category, determination test with R Square 0.570, and the regression equation can be explained Y=10.901+0.756X, which indicates that without a promotion, the results from employee performance of 10.901 and if X rises or falls by 1 number or if the promotion is increased or decreased by 1% then it will increase or decrease performance by 0.756%.